Palgrave advances in peace building critical developments and approaches - Richmond, Oliver P. (New York Palgrave Macmillan, 2010)
"The quality of the peace arrived at via liberal peace building approaches has been poor. The related state building praxis has generally been unable to respond to its critics. What is at stake is a recognition of peace buildings everyday political, social, economic, and cultural dynamics. This indicates the emergence of a post-liberal form of peace"--Provided by publisher.
Machine generated contents note: A Genealogy of Peace and Conflict Theory--O.Richmond PART I: CRITICAL AGENDAS: THEORIES, CONCEPTS, AND METHODS War, Government, Politics: A Critical Response to the Hegemony of the Liberal Peace--V.Jabri Reconstruction: The Missing Historical Link--A.Williams Method: Theory and Ethnography in Peace and Conflict Studies--J.Victorova Challenging State building as Peace building: Working with Hybrid Political Orders to Build Peace--V.Beoge, A. Brown, K. Clements &--A. Nolan Human Security and the Legitimization of Peace building--S.TadjbakhshGender and Peace building--T. Varynen Liberal Peace, Liberal Imperialism: A Gramscian Critique--I.Taylor The Ideology of Peace: Peace building and the War in Iraq--M.V.Rasmussen PART II: KEY AGENDAS: INSTITUTIONS, ISSUES AND THEMES The Institutionalization of Peace building: What Role for the UN Peacebuilding Commission?--A.Bellamy Democratization and Development: A Difficult Relationship--D.KotseNGO Dilemmas in Peace building--H.Carey Welfare in War-Torn Societies: Nemesis of the Liberal Peace?--M. Pugh Resolving Conflicts and Pursuing Accountability: Beyond Justice vs. Peace--C. Sriram Reconciliation (Reflections from Northern Ireland and South Africa)--J. Darby Training Goldfish (in a Desert): Transforming Political Economies of Conflict Using Voluntarism, Regulation and Supervision--N. Cooper PART III: DEVELOPING AGENDAS Culture: Challenges and Possibilities--M. Brigg Gilding the Lily? International Support for Indigenous and Traditional Peace building--R.Mac Ginty Kindered Peace building: Liberalism and Beyond--A.Watson Art and Peace building: How Theatre Transforms Conflict in Sri Lanka--N. Premaratna &--R. Bleiker Peace building and Environmental Challenges--F. Rotberg The State vs. the Terrorists vs. the People vs. the State and the Terrorists: Peace and Conflict in the Basque Country--I. Tellidis A Genealogy of Peace and Conflict Theory--O. Richmond PART I: CRITICAL AGENDAS: THEORIES, CONCEPTS, AND METHODS War, Government, Politics: A Critical Response to the Hegemony of the Liberal Peace--V. Jabri Reconstruction: The Missing Historical Link--A.Williams Method: Theory and Ethnography in Peace and Conflict Studies--J.Victorova Challenging State building as Peace building: Working with Hybrid Political Orders to Build Peace--V. Beoge, A.Brown, K.Clements &--A. Nolan Human Security and the Legitimization of Peace building--S.Tadjbakhsh Gender and Peace building--T.Varynen Liberal Peace, Liberal Imperialism: A Gramscian Critique--I. Taylor The Ideology of Peace: Peace building and the War in Iraq--M.V. Rasmussen PART II: KEY AGENDAS: INSTITUTIONS, ISSUES AND THEMES The Institutionalization of Peace building: What Role for the UN Peace building Commission?--A. Bellamy Democratization and Development: A Difficult Relationship--D.Kotse NGO Dilemmas in Peace building--H.Carey Welfare in War-Torn Societies: Nemesis of the Liberal Peace?--M. Pugh Resolving Conflicts and Pursuing Accountability: Beyond Justice vs. Peace--C. Sriram Reconciliation (Reflections from Northern Ireland and South Africa)--J. Darby Training Goldfish (in a Desert): Transforming Political Economies of Conflict Using Voluntarism, Regulation and Supervision--N.Cooper PART III: DEVELOPING AGENDAS Culture: Challenges and Possibilities--M.Brigg Gilding the Lily? International Support for Indigenous and Traditional Peace building--R.MacGinty Kindered Peace building: Liberalism and Beyond--A.Watson Art and Peace building: How Theatre Transforms Conflict in Sri Lanka--N.Premaratna &--R.Bleiker Peace building and Environmental Challenges--F.Rotberg The State vs. the Terrorists vs. the People vs. the State and the Terrorists: Peace and Conflict in the Basque Country--I.Tellidis.
Keywords: Peace-building.; Conflict management